FACTORS WHICH AFFECTING GAS RECOVERY AT GAS RESERVOIR WITH BOTTOM WATER DRIVE - D K (NIM : 12298015), ANDY
accordingly. Abandonment pressure represents the lowest reservoir pressure where the gas from reservoir can be produced with economic rate. If the gas reservoir has reached the abandonment condition then the reservoir is no longer economic to be produced. To determine the abandonment condition, two steps are applied to determine it. Those steps are reservoir simulation with simulator RZ2P and calculation of the wellhead pressure using the modified Cullender Smith method. The abandonment condition will reach if the well has reached the minimum wellhead pressure. Sensitivity test conducted to analyze the influence of some parameters to the abandonment condition. The sensitivitiy parameters include horizontal permeability, vertical permeability, strength of the aquifer, water viscosity, gas viscosity, and gas rate. The result of sensitivity test shows the effects of each parameter to abandonment condition.